The Effect of One-Sided Chewing Habits on the Occurrence of Caries, Calculus, and Oral Status Hygiene in Students of SMP Islam Terpadu Nurul Fadhilah, Percut Sei Tuan District, Deli Serdang Regency, Indonesia - Molek; Suci Erawati; Dina Fitriana (Community Medicine and Education Journal, 2024)
Worldwide, 45–97% of people chew food with only one side of their mouth. It is possible that chewing may act as a natural cleanser. One side of the mouth is more susceptible to the development of calculus and plaque when chewing, while the other side naturally removes debris and improves hygiene. Chewing behavior on one side causes a buildup of food detritus, resulting in low oral status. This study aims to explore the influence of one-sided chewing habits on the occurrence of caries, calculus, and oral status hygiene in Students of SMP Islam Terpadu Nurul Fadhilah Percut Sei Tuan District, Deli Serdang Regency, Indonesia. This study is an analytical observational research with a cross-sectional approach. This study uses primary data obtained from observations of the subject study. A total of 50 research subjects took part in this study. The incidence of caries, calculus, and oral hygiene status is influenced by one-sided chewing patterns. One-sided chewing patterns increase the caries index calculus index and reduce oral hygiene status.